Ocena występowania grzybni i owocników Phlebiopsis gigantea (Fr.: Fr.) Jülich w pniakach sosnowych po wykonaniu zabiegu ochronnego przed hubą korzeni - Małecka, Monika; Sierota, Zbigniew; Sikora, Katarzyna; Żółciak, Anna (Leśne Prace Badawcze, 2012)
Commercial preparations Rotstop and PgSuspension, used in Scandinavia and the United Kingdom, are EUlicensed biocontrol agents against root rot that contain isolates of the fungus Phlebiopsis gigantea. The composition of these two products differs from that of PgIBL, previously use in Poland, hence the need to verify their effectiveness under Polish site and stand conditions. Stumps were treated with the commercial products and subsequently checked after one year for the persistence of mycelia and fruiting bodies. Molecular methods were used on the mycelia present in the stumps to confirm that their genetic identity was consistent with fungal isolates from the preparations. Treatments with EU-licensed preparations gave satisfactory results – in about 70–80% of the stumps mycelia were present under the bark. Inoculation with Rotstop preparations was most effective during autumn 2008 (effectiveness of 82%), while PgSuspension application was most effective during spring 2008 (effectiveness of 77%). The development of the mycelia in pine stumps from the two preparations investigated (containing preserved dormant spores) was similar to that of preparation PgIBL (formulated from living mycelium within a growing medium), in terms of their relative effectiveness measured as the percentage of stumps supporting under-bark mycelia (which ranged between 70–90%, depending on the treatment term).